Mechanical tests and simulation on load sharing in alumina fiber bundles. Issue 10 (December 2015) - Neckel, L.; Pereira da Silva, J.G.; Guglielmi, P.; Hotza, D.; Al-Qureshi, H.A.; Montedo, O.R.K.; Bergmann, C.P.; Janssen, R.
Abstract: The mechanical behavior of bundles of ceramic fibers exhibits a characteristic rupture process when subjected to tensile known as avalanche failure. This process is related to the load sharing among fiber bundles once some of the elements begin to fail. Mechanical tests were performed with bundles and Weibull statistics was used to interpret the results of the maximum stress supported by the bundles before the avalanche failure. A computational simulation was originally adapted introducing load sharing models. The simulations were compared with experimental results. Finally, the newly proposed load model was considered to be a better approach for the understanding of the rupture avalanche effect.